2002
DOI: 10.1007/s00424-002-0967-x
|View full text |Cite
|
Sign up to set email alerts
|

Hypobaric hypoxia-reoxygenation diminishes band 3 protein functions in human erythrocytes

Abstract: We have previously shown that subjects exposed to acute hypobaric hypoxia display an erythrocyte membrane protein band 3 with an increased susceptibility to proteolytic degradation. We suggested it was due to an oxidative damage of band 3. We now report that exposure to hypobaric hypoxia followed by reoxygenation affects protein band 3 functions such as anion transport and binding of glyceraldehyde-3P-dehydrogenase. Transport capacity was assessed with the fluorescent probe 2-[N-(7-nitrobenz-2-oxa-1,3-diazol-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 29 publications
0
14
1
Order By: Relevance
“…Therefore, hypoxia seems to induce OS in lung (Wood et al 2000;Hoshikawa et al 2001;Minko et al 2002). Hypobaric hypoxia induced alterations of cell membrane structure and function appears to be mediated by OS (Celedo´n et al 1998;Behn et al 1999;Gonza´lez et al 2002). OS, therefore, may be involved in high-altitude-related pathology, like acute mountain sickness (Wood et al 2000;.…”
Section: Introductionmentioning
confidence: 91%
“…Therefore, hypoxia seems to induce OS in lung (Wood et al 2000;Hoshikawa et al 2001;Minko et al 2002). Hypobaric hypoxia induced alterations of cell membrane structure and function appears to be mediated by OS (Celedo´n et al 1998;Behn et al 1999;Gonza´lez et al 2002). OS, therefore, may be involved in high-altitude-related pathology, like acute mountain sickness (Wood et al 2000;.…”
Section: Introductionmentioning
confidence: 91%
“…7 Under hypoxic conditions, autooxidation of hemoglobin (Hb) is facilitated by an increased flux of superoxide radicals 8 and damage to membrane proteins may result from association of superoxide with Hb at reduced oxygen pressure. 6,9 In our earlier studies on rat erythrocytes, we have demonstrated that there is an increase in protein oxidation on exposure to intermittent hypobarichypoxia in trained rats and that the extent of increase in carbonyl content was greater at 6300 m than at 5700 m when compared to sedentary controls. 10 The present study was aimed at understanding the effect of intermittent hypobaric hypoxia (IHH) and antioxidants in ameliorating OS in erythrocytes of rats.…”
Section: Introductionmentioning
confidence: 95%
“…An extinction coefficient of 43. 6 Mcm À1 was used to determine enzyme activity. One unit is equivalent to 1.0 mole of H 2 O 2 degraded/min/mg Hb.…”
Section: Antioxidant Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors have observed that deoxygenation increases the degree of Tyr phosphorylation of band 3 in RBC (31) with an increase in glycolytic enzyme activities (11). Gonzalez et al (32) observed that exposure to hypobaric hypoxia followed by reoxygenation induced inhibition of band 3 anion transport function and a decrease in binding of G3PDH to band 3. In the present study, we observed increased G3PDH Tyr-phosphorylation in neonatal RBC samples after 16 h of hypoxic incubation as well as after 8 h of reoxygenation with respect to starting level at time 0.…”
mentioning
confidence: 99%